Does communication skills training make a difference to patients' experiences of consultations in oncology and palliative care services?. Issue 2 (1st November 2012) - Johnson, L.A.; Gorman, C.; Morse, R.; Firth, M.; Rushbrooke, S.
<x xml:space="preserve">Abstract</x> There is much evidence supporting the efficacy of communication skills training; however, very little of this evidence comes from patient feedback. The primary aim of this pilot study was to evaluate whether the advanced communications skills training improves patients' experience of consultations. Healthcare professionals working in oncology and palliative care services from the North East of England were invited to participate in this study. Interactions between healthcare professionals (n = 21) and patients (n = 1103) were evaluated using the Consultation and Relational Empathy (CARE) Measure, which is a brief questionnaire designed to assess the patients' perceptions of relational empathy in the consultation. Additional demographic variables, such as patient age, length of consultation, familiarity with healthcare professional and overall satisfaction with consultation, were also collected. Healthcare professionals were either part of the intervention group who attended a 3‐day communication skills training course or part of the control group who were on the waiting list for training. No differences in the patients' ratings on the CARE measure were found between Time 1 (before training) and Time 2 (after training) for the intervention group. Possible explanations for the findings are explored and implications for communication skills training are discussed.